Patients’ experience regarding informed consent in elective and emergency surgeries - Olivera Perić; Marinko Mišić; Dejan Tirić; Nikolina Penava; David Bušić; Vajdana Tomić (Medicinski glasnik, 2018)
Aim: To examine whether there are differences in the experience in giving informed consent of patients whose surgery was elective compared to emergency surgery in the same department. Methods: A prospective cross-sectional study was conducted in the Department of Gynaecology and Obstetrics of University Clinical Hospital Mostar during a 6-month period. The sample of respondents consisted of two groups of patients, 145 with elective surgery and 90 patients with emergency surgery. The study was conducted using an anonymous questionnaire. Results: Patients in both examined groups were equally satisfied with the procedure of informed consent. Most patients signed the informed consent at the request of a nurse, 195 (83%). During the process of consenting, almost all patients, regardless of whether they had elective or emergency surgery, claimed that they understood the form, which had to be signed, it was important to them, 230 (97.9%), except the patients who had elective surgery, 130 (90.3%), regularly stated that having an opportunity to ask questions was important to them. Respondents with emergency surgery more frequently agreed to sign whatever was in the form, 42 (46.7%). Conclusion: Patients who had a planned surgery and patients who had an urgent surgery, mostly declare contentment with the use of informed consent although they did not have the same experience about informed consent.
Keywords: consent form; understanding of consent; patient satisfaction